Rancang Bangun Aplikasi Edukasi Interaktif Cerita Rakyat ‘Keong Mas’ Berbasis Augmented Reality Menggunakan Unity 3D - Asa Yuaziva (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
The purpose of this research is to create an interactive Augmented Reality (AR)-based educational application that can display the Indonesian folktale "Keong Mas" using Unity 3D and Vuforia SDK. Due to the dominance of modern digital entertainment that is more visually appealing, the younger generation's interest in traditional folktales is declining. The choice of AR technology is based on its ability to combine three-dimensional virtual objects with the real environment in real-time, resulting in an interactive, engaging, and memorable learning experience. The research process used is the Life Cycle of Multimedia Development (MDLC), which consists of six stages: ideation, design, material collection, compilation, testing, and deployment. 3D character models, background environments, and interactive stories appear in the application when the camera detects certain markers. Testing was conducted using the black-box method to ensure all functions, including marker tracking, scene transitions, and narration playback, run smoothly. The test results show that the AR application "Keong Mas" successfully displays the folktale interactively and engagingly, thereby increasing the learning interest of children and adolescents. This application not only serves as an innovative learning medium but also contributes to the preservation of local culture through the integration of digital technology.